2019
DOI: 10.1038/s41598-019-53707-z
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of chimeric peptides as antagonists for the G protein-coupled receptor, RXFP4

Abstract: Insulin-like peptide 5 (INSL5) is a very important pharma target for treating human conditions such as anorexia and diabetes. However, INSL5 with two chains and three disulfide bridges is an extremely difficult peptide to assemble by chemical or recombinant means. In a recent study, we were able to engineer a simplified INSL5 analogue 13 which is a relaxin family peptide receptor 4 (RXFP4)-specific agonist. To date, however, no RXFP4-specific antagonist (peptide or small molecule) has been reported in the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
(70 reference statements)
1
4
0
Order By: Relevance
“…INSL5-A13AGP also demonstrated antagonism but with a lower potency than INSL5-A13NR, whereas INSL5-A13HR had no antagonist activity. Consistent with the small agonistic effect of INSL5-A13NR, the peptide was not able to completely block the cAMP inhibitory effects of an agonist in a similar manner to the antagonism we have recently demonstrated for the nonspecific RXFP3/4 antagonist, ΔR3/I5 . To further demonstrate the RXFP4 antagonist activity of INSL5-A13NR, we developed a sensitive NanoBRET based β-Arrestin2 recruitment assay.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…INSL5-A13AGP also demonstrated antagonism but with a lower potency than INSL5-A13NR, whereas INSL5-A13HR had no antagonist activity. Consistent with the small agonistic effect of INSL5-A13NR, the peptide was not able to completely block the cAMP inhibitory effects of an agonist in a similar manner to the antagonism we have recently demonstrated for the nonspecific RXFP3/4 antagonist, ΔR3/I5 . To further demonstrate the RXFP4 antagonist activity of INSL5-A13NR, we developed a sensitive NanoBRET based β-Arrestin2 recruitment assay.…”
Section: Discussionsupporting
confidence: 88%
“…Because INSL5-A13NR only demonstrates partial antagonism in this cAMP activity assay, similar to the RXFP3/4 antagonist ΔR3/I5, we also assessed the ability of INSL5-A13NR to antagonize agonist-induced β-Arrestin recruitment. It has been previously demonstrated that agonist activation of RXFP4 leads to the recruitment of both β-Arrestin1 and β-Arrestin2 leading to receptor internalization .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A13 and its two truncated analogs (A13: B3− 24, A13: B5−24) showed random coil structures in 10 mM phosphate buffer (PB) (Figure 3A). As previous study of INSL5-related peptides revealed that the α-helical structure could be induced by trifluoroethanol (TFE), 22 thus, we further studied the CD spectroscopy of A13: B3−24 and A13: B5−24 in phosphate buffer containing 20% TFE. TFE is known to improve hydrogen bonding of peptides and proteins and thus stabilizes the α-helical structure of peptide.…”
mentioning
confidence: 99%